Epidemiological study on reproductive pathogens with particular focus on Bovine Viral Diarrhoea Virus in dairy cattle in Tajikistan - Lindahl, Elisabeth (SLU/Dept. of Biomedical Sciences and Veterinary Public Health (until 231231), 2008)
Bovine Viral Diarrhoea Virus (BVDV) is considered to be one of the most important infectious diseases of cattle. It causes substantial economic losses worldwide mainly due to reproductive disorders. Neospora caninum and Brucella abortus are other important diseases causing major economic losses due to reproductive failure. B. abortus is also an important zoonotic disease and many countries, like Tajikistan, have a vaccination program in order to control the disease. Tajikistan, located in Central Asia, is a country where approximately 80% of the households own livestock. Many people are dependent on their cattle for survival. Reproductive disorders among cattle can therefore be greatly disadvantageous to the work on reducing poverty in the country.